\(a^{100}+b^{100}=a^{101}+b^{101}\Leftrightarrow a^{100}-a^{101}=b^{101}-b^{100}\Rightarrow a^{100}\left(1-a\right)=b^{100}\left(b-1\right)\)
\(\Rightarrow-a^{100}\left(a-1\right)=b^{100}\left(b-1\right)\)
1./ Nếu b = 1 => a = 1 (do a;b>0) nên tổng S = a2010 + b2010 = 2
2./ Nếu b khác 1 \(\Rightarrow\frac{a-1}{b-1}=\frac{b^{100}}{a^{100}}=\left(\frac{b}{a}\right)^{100}\)(1)
Tương tự từ: \(a^{102}+b^{102}=a^{101}+b^{101}\Leftrightarrow a^{102}-a^{101}=b^{101}-b^{102}\Rightarrow a^{101}\left(a-1\right)=b^{101}\left(1-b\right)\)
\(\Rightarrow\frac{a-1}{b-1}=\frac{b^{101}}{a^{101}}=\left(\frac{b}{a}\right)^{101}\)(2)
Từ (1) và (2) \(\left(\frac{b}{a}\right)^{100}=\left(\frac{b}{a}\right)^{101}\Rightarrow\frac{b}{a}=1\Rightarrow a=b\)
Từ: a100 + b100 = a101 + b101 => 2a100 = 2 a101 => a100 = a101 => a = 1; b = 1
Và tổng S = a2010 + b2010 = 2.
ở chổ (1) sai dấu của a mũ 100 rồi bạn ơi